2020
DOI: 10.1140/epjc/s10052-020-7778-0
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigations on formations of hairy neutral reflecting shells in the scalar-Gauss–Bonnet gravity

Abstract: We study scalarization of spherically symmetric neutral reflecting shells in the scalar-tensor gravity. We consider neutral static massless scalar fields non-minimally coupled to the Gauss-Bonnet invariant. We obtain a relation representing the existence regime of hairy neutral reflecting shells.For parameters unsatisfying this relation, the massless scalar field cannot exist outside the neutral reflecting shell. In the parameter region where this relation holds, we get analytical solutions of scalar field hai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In particular, Hod derived a remarkably compact resonance formula for the allowed masses of the spatially regular scalar fields supported by charged shell configurations. In the background of neutral horizonless reflecting shells, exterior scalar fields also can exist when including non-minimally couplings between scalar fields and the Gauss-Bonnet invariant [36]. Inspired by analysis in [35], we plan to carry out an analytical investigation on configurations composed of scalar fields and neutral reflecting shells in the scalar-Gauss-Bonnet gravity.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Hod derived a remarkably compact resonance formula for the allowed masses of the spatially regular scalar fields supported by charged shell configurations. In the background of neutral horizonless reflecting shells, exterior scalar fields also can exist when including non-minimally couplings between scalar fields and the Gauss-Bonnet invariant [36]. Inspired by analysis in [35], we plan to carry out an analytical investigation on configurations composed of scalar fields and neutral reflecting shells in the scalar-Gauss-Bonnet gravity.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the Schwarzschild and RN black holes in a cavity have quite similar phase structure and transition to these of the AdS counterparts. Afterwards, various black brane systems [78][79][80][81][82][83], a Gauss-Bonnet black hole [84], hairy black holes [85][86][87][88], and boson stars [89][90][91][92] in a cavity were extensively investigated, and it was also shown that the behavior of the gravity systems in a cavity is strikingly similar to that of their counterparts in AdS gravity. However, we have recently studied the phase structure of Born-Infeld black holes enclosed in a cavity [93,94] and thermodynamic geometry of RN black holes in a cavity [95] and found their behavior is dissimilar from that of the corresponding AdS black holes.…”
Section: Introductionmentioning
confidence: 99%